Study of population exposure to air pollutants in transport in an urban environment: review article - Correia, Ana Margarida (2021)
Air pollution is caused by several anthropogenic factors and has consequences for human health. Motor vehicles are one of the main sources of anthropogenic emissions of atmospheric pollutants. Carbon monoxide, particulate matter, and nitrogen oxides are some of the main air pollutants responsible for the degradation of the air quality in urban areas. The transport most used in major cities in Portugal are bus, bicycle, car, and subway. Through a review of studies from various parts of the world, it was found that the car and the subway are the transports with the highest concentrations of atmospheric pollutants, while the bus was the transport with the lowest concentrations in relation to all the pollutants analyzed. High concentrations of each pollutantare dependent on different factors such as increased traffic density, location of the exhaust pipes of vehicles, the ventilation conditions, wear of the wheels of the rail and the braking system, the proximity of bicycle paths to traffic lanes, among others. It was also found that the bicycle is the means of transport that involves the highest inhaled doses, although it is the most beneficial means of transport for health. It is, therefore, necessary to properly define the location of bike paths and adopt measures such as the use of barriers between the roadway and bike paths.